Enhanced magnetic ordering temperature and dielectric behavior in off-stoichiometric Ca3Cu1−xMn1+xO6 (x=0.07). (December 2015) - Rayaprol, S.; Kaushik, S.D.; Iyer, K.K.; Sampathkumaran, E.V.
Abstract: A marginally Cu deficient compound Ca3 Cu0.93 Mn1.07 O6, derived from Ca3 CuMnO6 was studied for its structural and magnetic properties using magnetization, heat capacity, dielectric studies and neutron diffraction. Interestingly enough, this off-stoichiometry leads to long-range magnetic order at a much higher temperature of ~23 K, compared to that reported (5.3 K) for the stoichiometric compound, thereby strengthening our earlier proposal that this system is an example for an 'order by disorder' phenomenon. It is also intriguing to note that another anomaly is observed in ac susceptibility and dielectric measurements around 110 K, which has not been observed in the stoichiometric compound and we attribute to intrachain interactions. The magnetic structure of Ca3 Cu0.93 Mn1.07 O6 obtained from the analysis of temperature-dependent neutron diffraction data is found to be of a ferrimagnetic type. Ca3 Cu0.93 Mn1.07 O6 also exhibits dielectric anomalies in the vicinity of the two magnetic ordering temperatures. Overall, this off-stoichiometric composition presents an interesting situation in comparison with the literature results on stoichiometric composition. Highlights: Off-stoichiometric title compound exhibits long-range magnetic order at a much higher temperature compared to the stoichiometric compound. Anomaly in dielectric and ac susceptibility measurements observed has been attributed to intrachain interactions. Ferrimagnetic structure observed from the neutron diffraction measurements. Only Cu site atoms are found to be magnetic. Mn site atoms exhibit no magnetic moment.